618 Benefit of Prenatal Diagnosis of Complex Congenital Heart Defects on Neonatal Morbidity. (October 2012) - Ruijsink, B; Landsman, F; Slieker, M; Vijlbrief, D; Heide, H ter; Boode, W de; Jansen, K; Freund, M
Abstract : Background and Aims: As survival rates in neonatal cardiac surgery improve over time, morbidity becomes more important in complex congenital heart disease (cCHD). We investigated whether prenatal diagnosis of cCHD affects preoperative and early postoperative morbidity in neonates. Methods: Retrospective observational study, performed between July 1 st 2004 and July 1 st 2011, including 247 infants with cCHD requiring surgery within the neonatal period. 113/247 patients were diagnosed with cCHD by prenatal screening (PreDx). Morbidity was based on preoperative use of high dose prostaglandin E and pre- and postoperative cardiac function, ventilation time, length of admission (LOF), inotropic support requirement and presence of severe complications (resuscitation, acute kidney and liver injury, and neurological events). Results: Complexity of cCHD was higher in children diagnosed PreDx. After correction of complexity, median pre-operative ventilation time (3 vs 0 days), LOF (7 vs 9 days) and preoperative cardiac function were significantly better in PreDx neonates; and correction of acidosis, preoperative inotropic support and high dose prostaglandin E was significantly less common. Severe complications occurred significantly less when PreDx. There were no significant differences in postoperative morbidity and overall mortality. Conclusions: Prenatal diagnosis of cCHD improves pre-operative morbidity significantly. The patient condition is better compared to postDx and the need for preoperative intensive care treatment is less. Seemingly, intensive care treatment can achieve a good pre-operative condition, even in neonates deteriorated due to an at birth unknown cCHD. This could explain why post-operative morbidity was equal in both groups.